Short‐term Impacts on Soil‐quality Assessment in Alternative Land Uses of Traditional Paddy Fields in Southern Brazil. (11th November 2016) - Martins, Amanda Posselt; Denardin, Luiz Gustavo de Oliveira; Borin, José Bernardo Moraes; Carlos, Filipe Selau; Barros, Thiago; Ozório, Dânia Vieira Branco; Carmona, Felipe de Campos; Anghinoni, Ibanor; Camargo, Flávio Anastácio de Oliveira; Carvalho, Paulo César de Faccio
Abstract: No‐till, crop diversity and integrated crop–livestock systems are proposed managements to increase agriculture sustainability in the rice paddies of the Southern Brazilian lowlands and avoid degradation in the region. Because soil is considered a key medium in which management modifications can be measured, our study aimed to evaluate soil‐quality impacts by measuring carbon and nitrogen stocks and microbial activity 18 months after the adoption of different paddy‐farming systems in an Albaqualf soil of Southern Brazil. The treatments consisted of five paddy‐farming systems with a range of vegetation diversity (both in time and in space) and grazing seasons. In addition, a reference area (i.e. native forest) was sampled for comparison. We verified that soil quality was affected over the short term through the adoption of no‐till, crop diversity and integrated grazing practices. However, during the study period, only the system with low anthropic and/or mechanical intervention and high plant diversity differed from the traditional paddy land‐use approach in Brazil in terms of soil‐quality effects. This system achieved a carbon management index of 49 (approximately half that of the native forest) and had the highest enzymatic activity (similar to native forest). These outcomes were primarily due to an increase in the particulate organic matter fraction of the soil carbon stock (4·6 Mg ha −1 more than in rice monocropping). To evaluate changes in soil quality over the long term, additional studies are required. Copyright © 2016 John Wiley & Sons, Ltd.